2022
DOI: 10.4103/ijo.ijo_1920_21
|View full text |Cite
|
Sign up to set email alerts
|

Digital eye strain and its associated factors in children during the COVID-19 pandemic

Abstract: Purpose: This study was undertaken to identify the prevalence of symptoms related to the use of display devices and contributing factors in children engaged in distance learning during the COVID-19 pandemic. Methods: An online electronic survey form was prepared using Google Forms (Alphabet Co., Mountain View, CA) and sent to parents of children under the age of 18 years engaged in distance learning during the COVID-19 pandemic. The types of display devices children use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 16 publications
1
29
0
1
Order By: Relevance
“…Hence, digital device usage increased throughout the world, exacerbating DES symptoms. DES prevalence amongst children alone rose to 50-60% in the COVID-19 era [44][45][46]. In children, the symptoms expanded to include recent onset esotropia and vergence abnormalities as part of the DES spectrum [47,48].…”
Section: Burden Of Des and Associated Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, digital device usage increased throughout the world, exacerbating DES symptoms. DES prevalence amongst children alone rose to 50-60% in the COVID-19 era [44][45][46]. In children, the symptoms expanded to include recent onset esotropia and vergence abnormalities as part of the DES spectrum [47,48].…”
Section: Burden Of Des and Associated Conditionsmentioning
confidence: 99%
“…2022 Apr; 19(7): 3996 [ 53 ] Thailand 527 students, 70.40% females, mean age 20.04 ± 2.17 years Female gender, atopic eye disease, dry eyes, itching, red eye, eye pain, astigmatism, previous refractive surgery, tear substitute use, contact lens use, mobile and tablet use Eye pain-96.5%, burning sensation-92.5%, headache 90.08%, defective vision-15.95 CVS-Questionnaire (CVS-Q), CVS was diagnosed with a score of CVS-Q ≥ 6 Prevalence of CVS was 81%, distance less than 20 cm (52.7 vs. 40%), less brightness less 14.8 vs. 7.0%) and glare or reflection on display (47.8 vs. 29.0%) were associated with CVS Social distancing is mandatory, online classes are unavoidable, increased screen was associated with increases prevalence of CVS. Laptop/desktop should be preferred over mobile phone 2 Cai et al Front Med (Lausanne), 2022 Mar 21;9:853293 [ 54 ] China 115 children with myopia Strict home confinement, hereditary, closed indoor work time, excess exposure to electronic gadgets Protective factors- age, rest time, sleep time, and distance from the device while usage Asthenopic symptoms Axial length assessment (IOL Master 700) and refractive errors (without cycloplegia), visual function, convergence insufficiency symptom survey (CISS) and eye care habits questionnaire Axial length elongation was 35% higher than normal, positively correlated with severe asthenopia ( r = 0.711), negative with age ( r = − 0.442), distance from eyes (− 0.238) Decreased outdoor activities and increased screen time accelerated myopia progression by 1/3 3 Demirayak et al Indian J Ophthalmol 2022 Mar;70(3):988–992 [ 45 ] Turkey 692 children under the age of 18 years, mean age 9.72 ± 3.02 years, 360 (52%) were girls, 62.57% were students in primary school Computer use (61.7%), smartphones (57.8%), mean duration of display device use 71.1 ± 36.02 min Headache (52.2%), eye fatigue (49.3%), and eye redness (49.3%) and double vision-8.8% Online electronic survey using Google Forms 48.2% experienced 3 or more symptom, male gender and age were independent risk factors for 3 or more symptoms Digital device use during the pandemic exacerbated the DES among children 4 Basnet et al JNMA J Nepal Med Assoc, 2022 Jan 15;60(245):22–25 [ 55 ] Nepal 318 subjects Digital device use, tablet use, computer, and smartph...…”
Section: Burden Of Des and Associated Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study found that a screen distance less than 40 cm is significantly associated with eye fatigue [ 12 ]. In our study, the average screen distance was 36.29 cm ± 5.19, suggesting a much shorter distance from current recommendations (50-100 cm), which is another important risk factor for CVS.…”
Section: Discussionmentioning
confidence: 99%
“…The use of artificial light has also been shown to be significantly correlated with eye strain, redness, and tearing [ 12 ]. In the present study, the preferred type of lighting was artificial light (52.9%), which highlighted the association between ambient lighting and eye symptoms.…”
Section: Discussionmentioning
confidence: 99%